Catecholaminergic Polymorphic Ventricular Tachycardia in a 16-year-old: Case Report - John Wahhab; Ani Oganesyan; Krishi Korrapati (Clinical Practice and Cases in Emergency Medicine)
Introduction: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a rare, inheritable cardiac disorder associated with stress- or exercise-induced syncope or cardiac arrest in children and young adults. Diagnosis of CPVT is often missed or delayed due to variable presentation and normal cardiac imaging and electrocardiogram results, with about 40% of patients dying within 10 years of diagnosis. This case underscores the importance of cross-departmental communication when managing complex pediatric cases, especially when using an interpreter. Case Report: A 16-year-old male presented to the hospital with cardiac arrest in ventricular fibrillation following collapse despite a history of treatment with flecainide and nadolol. He was resuscitated, stabilized with antiarrhythmic drips, received an implantable cardioverter defibrillator, and was discharged neurologically intact nine days later. It is vital for physicians to consider CPVT in young patients with syncope to prevent errors in diagnosis of this highly fatal disease. Conclusion: Catecholaminergic polymorphic ventricular tachycardia is a rare genetic disease with significant morbidity and mortality. Treatment decisions for acute CPVT often occur without prior knowledge of the disease; so, in patients diagnosed with CPVT, physicians should implement appropriate therapeutic options to prevent future cardiac events. For patients who remain symptomatic despite compliance with beta blockers and/or other antiarrhythmic therapy, interventions such as placement of an implantable cardioverter defibrillator or sympathetic denervation may be necessary to prevent life-threatening arrhythmias. This case also underscores the importance of obtaining a detailed family history and coordinating care with other physicians in cases where history is limited.